Pengaruh Likuiditas Dan Leverage Terhadap Kebijakan Dividen Dimoderasi Oleh Ukuran Perusahaan - PURBA, RENI OKTAVIA; SURYANI, YANI (UNIVERSITAS DHARMAWANGSA, 2025)
The study aims to determine the effect of liquidity and leverage on dividend policy with firm size as a moderating variable. This research is a type of quantitative associative study with a causal comparative relationship. The population in this study consists of food and beverage companies listed on the IDX for the period 2019-2023. The sample selection was conducted using a purposive sampling method, resulting in 14 companies that met the criteria with 5 years of observation, bringing the total sample to 70. The data collection technique was carried out through documentation study using the official website of the IDX, namely www.idx.co.id. The analysis technique used is multiple linear regression analysis and residual test. The result of this study indicate that liquidity and leverage don’t have a significant effect on dividend policy. Firm size is able to moderate the influence of luquidity and leverage on dividend policy in food and beverage companies listed on the IDX during 2019-2023.